2006
DOI: 10.1093/jee/99.5.1854
|View full text |Cite
|
Sign up to set email alerts
|

Categories and Inheritance of Resistance to Russian Wheat Aphid (Homoptera: Aphididae) Biotype 2 in a Selection from Wheat Cereal Introduction 2401

Abstract: The Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Homoptera: Aphididae), is one of the most devastating insect pests of wheat (Triticum spp.) and barley (Hordeum spp.) in the world. Yield losses and control costs are valued at several hundred million dollars each year. The use of D. noxia-resistant cultivars is an ecologically, economically, and biologically sound method of managing this pest. Several D. noxia resistance (Dn) genes from wheat have been used to develop cultivars resistant to D. noxia. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 31 publications
8
21
0
3
Order By: Relevance
“…This suggests the presence of a second gene with minor effect contributing to resistance in CI2401. This result is supported by the previous study of Voothuluru et al (2006) suggesting the likely presence of two genes conferring resistance in CI2401 based on segregation of F 2 and F 4 progenies from a cross between CI2401 and the susceptible parent 'Karl'. This minor gene effect was possibly not detected in our inheritance studies using F 2 and F 3 populations because chlorosis and leaf rolling scores were combined to categorize the responses as resistant or susceptible.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This suggests the presence of a second gene with minor effect contributing to resistance in CI2401. This result is supported by the previous study of Voothuluru et al (2006) suggesting the likely presence of two genes conferring resistance in CI2401 based on segregation of F 2 and F 4 progenies from a cross between CI2401 and the susceptible parent 'Karl'. This minor gene effect was possibly not detected in our inheritance studies using F 2 and F 3 populations because chlorosis and leaf rolling scores were combined to categorize the responses as resistant or susceptible.…”
Section: Discussionsupporting
confidence: 86%
“…Voothuluru et al (2006) also reported the likely presence of two dominant genes conferring resistance to RWA2 in CI2401. As pointed out by Voothuluru et al (2006), one of the genes could not be Dn4 since RWA2 is virulent to Dn4. The resistance gene(s) in CI2401 have not been genetically mapped.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of our antixenosis assays are in agreement with those of Voothuluru et al (2006) and detected no (Lage et al 2004;Miller et al 2003). However, Randolph et al (2005) noted no antixenosis among several D. noxia-resistant wheat cultivars.…”
Section: Discussionsupporting
confidence: 87%
“…It was previously reported that S6A maintained a normal accumulation of dry matter in aerial and root parts when subjected to greenbug infestation with values similar to those in uninfested controls (Castro et al 2007). Voothuluru et al (2006) also reported that tolerance to RWA biotype 2 in line Cltr2401 was based on the maintenance of root dry weight under infestation. The DHR mean values for ADWC and RDWC were between the parental lines, indicating additive eVects on trait expression.…”
Section: Discussionmentioning
confidence: 97%